Pagamentos por meio de aplicativo de mensagens - Liu, Xugui (2017)
This project seeks to investigate the Paggi case, the first and only company that currently adopts payments through the messaging application in Brazil. This payment model leveraged the critical mass of messaging application users and thus achieved a lot of success in China. Besides China, countries like the United States and India are also beginning to implement this payment model. Thus, it is interesting to study this pioneering case in Brazil, where there is a high demand for the use of messaging applications. The main objective of this work is to discover the similarities and differences in the evolution of the payment model through the messaging application between the two companies selected from Brazil and China through the short-term evolutionary metrics. To Achieve this objective, interviews, documents, and publications analyzes were carried out to compare the similarities and differences regarding the evolution of the payment model of the two companies. It is hoped that the results found in this study could contribute to those interested in the Mobile Payments market, including those called Fintechs and also the messaging application companies that are looking to expand their platform and service lines, as follows: (1) to better understand the similarities and differences in the business model and the evolution of payment through messaging application between suppliers in these countries, (2) to offer recommendations for new entrants in this market in Brazil, to better structure their value propositions to customers, and (3) to identify the difficulties and facilities to implement this mobile payment model in the Brazilian market.